Fish species composition in the Kaliotik River, Lamongan Regency, Indonesia - Fuquh Rahmat Shaleh; Agung Pamuji Rahayu; Nuralim Pasisingi (Gorontalo State University, 2020)
This research aimed to determine the species composition of fishes in the Kaliotik River, Lamongan Regency. The sampling was conducted from March to May 2020 at four stations. A total of 1031 samples caught by the fishing net during the study consists of Anabas testudineus, Trichogaster trichopterus, Hyposarcus pardalis, Mystus sp., Channa striata, Oreochromis mossambicus. The fish diversity index values indicated that the river is in low to moderate condition. The species was also slightly evenly distributed in the waters with no dominant species. Trichogaster sp. and Anabas testudineus are the two dominant species found in the waters with a relative abundance of 44 % and 41 %, respectively. The Kaliotik River ecosystem balance was affected by disposal from human activities along the riverbank.